Validation of dynamic risk stratification and impact of BRAF in risk assessment of thyroid cancer, a nation-wide multicenter study - Pérez-Fernández, Laura; Sastre, Julia; Zafón, Carles; Oleaga, Amelia; Castelblanco, Esmeralda; Capel, Ismael; Galofré, Juan C.; Guadalix-Iglesias, Sonsoles; De la Vieja, Antonio; Riesco-Eizaguirre, Garcilaso (Frontiers in Endocrinology, 2023)
Introduction The dynamic risk stratification (DRS) is a relatively new system in thyroid cancer that considers the response to primary treatment to improve the initial risk of recurrence. We wanted to validate DRS system in a nationwide multicenter study and explore if the incorporation of BRAFV600E into DRS helps to better categorize and predict outcomes. Materials and Methods, Retrospective study of 685 patients from seven centers between 1991 and 2016, with a mean age of 48 years and a median follow-up time of 45 months (range 23-77). The overall BRAFV600E prevalence was 53.4%. We classified patients into four categories based on DRS (‘excellent’, ‘indeterminate’, ‘biochemical incomplete’, and ‘structural incomplete’ response). Cox regression was used to calculate adjusted hazard ratios (AHR) and proportions of variance explained (PVEs). Results We found 21.6% recurrences and 2.3% cancer-related deaths. The proportion of patients that developed recurrence in excellent, indeterminate, biochemical incomplete and structural incomplete response to therapy was 1.8%, 54%, 91.7% and 96.2% respectively. Considering the outcome at the end of the follow up, patients showed no evidence of disease (NED) in 98.2, 52, 33.3 and 25.6% respectively. Patients in the structural incomplete category were the only who died (17.7%). Because they have similar outcomes in terms of NED and survival, we integrated the indeterminate and biochemical incomplete response into one unique category creating the 3-tiered DRS system. The PVEs of the AJCC/TNM staging, ATA risk classification, 4-tiered DRS, and 3-tiered DRS to predict recurrence at five years were 21%, 25%, 57% and 59% respectively. BRAFV600E was significantly associated with biochemical incomplete response (71.1 vs 28.9%) (HR 2.43; 95% CI, 1.21 to 5.23; p=0.016), but not with structural incomplete response or distant metastases. BRAF status slightly changes the AHR values of the DRS categories but is not useful for different risk grouping. Conclusions This is the first multicenter study to validate the 4-tiered DRS system. Our results also show that the 3-tiered DRS system, by integrating indeterminate and biochemical incomplete response into one unique category, may simplify response to therapy keeping the system accurate. BRAF status does not provide any additional benefit to DRS.